Smart Contracts for Subscription Management in Information Services - MohamadAbbas, Haydeer; Chandrasekharan, G.; Paranthaman, Prabakaran; Anvarovna, Abdullayeva Shakhnoza; Rajapriya, M.; Udayakumar, R. (Indian Journal of Information Sources and Services, 2025)
The integration of blockchain technology introduced smart contracts, which revolutionized the automation and security of executing transactions. This article focuses on using smart contracts to manage information service subscriptions where reliability, transparency, and efficiency are required. Subscription management suffers from payment delays, trust issues, errors, and many other problems. Through automation and smart contracts, the self-executing nature of these agreements helps organizations streamline subscriptions, enforce terms with less risk, and greatly reduce operational blunders. Blunders. In this paper, I thoroughly review smart contracts, explore current gaps within subscription management, and explain how integrating blockchain can fill them. Some successful implementations are presented as case studies. Others discuss technical and organizational hurdles for practical adoption. Future scope widens by providing insight into blockchain-based decentralized solutions' role in contemporary subscription-centered business models. The research ends by recommending information service providers adopt smart contracts for better operational efficiency, reduced costs, and stronger customer relations.